THE INFLUENCE OF BANK LENDING, OVERDRAFT FACILITIES, AND OWNERS EXPERIENCE ON REINVESTMENT (Study on MSME Actors in Lhokseumawe City) - Nadia Hasely; Rico Nur Ilham; Iklil; Tari Mardhia; Alfaiza (Universitas Efarina, 2022)
The aim of this research is to determine the influence of bank lending, overdraft facilities, and owners experience on reinvestment. The method used is quantitative, the population is MSME actors in Lhokseumawe City, while the number of samples used is 100 respondents, the data used is primary data from the results of questionnaires, data analysis uses multiple linear regression and hypothesis testing. The results of this research show that bank lending has a positive and significant effect on reinvestment in Lhokseumawe City MSMEs, this is because the significance value is 0.000 < 0.05. Overdraft facilities have a negative and insignificant effect on reinvestment in Lhokseumawe City MSMEs, this is because the significance value is 0.147 <0.05. Owners experience has a positive and significant effect on reinvestment in Lhokseumawe City MSMEs, this is because the significance value is 0.000 < 0.05. Bank lending, overdraft facilities, and owners experience simultaneously and significantly influence reinvestment in Lhokseumawe City MSMEs, this is because the significance value is 0.000 < 0.05.